KARAKTERISTIK THERMOLUMINESCENT DOSIMETERS UNTUK DOSIMETRI IN VIVO PADA RADIOTERAPI EKSTERNA - Mursiyatun Mursiyatun; Evi Setiawati; Zaenul Muhlisin (Youngster Physics Journal, 2014)
The Characteristics of Thermoluminescent Dosimeters (TLD) for in vivo dosimetry in external radiotherapy have been examined. The research was intended to determine the TLD calibration factor and TLD correction factors to various radiation doses, source surface distance (SSD), size field and angle of incidence so that the TLD can be beneficial for in vivo dosimetry. TLD was placed on the surface of solid water phantom and ionization chamber at the reference depth (10 cm). Then was irradiated using 6 MV photons with variation in radiation doses, SSD, size field and angle of incidence. The research  resulted in the TLD calibration factor (4,26 + 0,3) x 10-2 cGy/nC. The value of TLD correction factors at the number of MU 100, SSD 100 cm, size field 10 x 10 cm2 and angle of incidence 00 was 1.Keywords: Thermoluminescent Dosimeters (TLD), in vivo dosimetry, calibration factor, correction factor